1980
DOI: 10.1177/000306518002800205
|View full text |Cite
|
Sign up to set email alerts
|

Reflections On Some Current Controversies In Psychoanalysis

Abstract: Recently published reports about completed analyses conducted by competent students with expert supervision permit us to compare two contrasting clinical traditions within psychoanalysis, that proposed by Heinz Kohut over the past decade and a conservative point of view sharply focused on elucidation of derivatives of the infantile neurosis. Analytic treatment based on each set of these theoretical assumptions will achieve valuable results--very different in kind in each instance. On the other hand, elucidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Freud, 1894S. Freud, /1962Gedo, 1980;Higgins, 1987;Horowitz, Markman, Stinson, Fridhandler, & Ghannam, 1990;Klein, 1976;Lockhard & Paulhus, 1988;Moreland & Sweeny, 1984;Perry, 1993;Rogers, 1957;Sackeim & Gur, 1979, 1985Shapiro, 1989;Swann, Stein-Seroussi, & McNulty, 1992;Vaillant, 1992;Weinberger, 1990;Wylie, 1979). The result is that indi-viduals often limit their awareness to include only those experiences congruent with, or distort representations of their experience to sustain, their conscious concept of self (S. Freud, 1914Freud, /1957Kernberg, 1967;Rogers, 1951).…”
mentioning
confidence: 99%
“…Freud, 1894S. Freud, /1962Gedo, 1980;Higgins, 1987;Horowitz, Markman, Stinson, Fridhandler, & Ghannam, 1990;Klein, 1976;Lockhard & Paulhus, 1988;Moreland & Sweeny, 1984;Perry, 1993;Rogers, 1957;Sackeim & Gur, 1979, 1985Shapiro, 1989;Swann, Stein-Seroussi, & McNulty, 1992;Vaillant, 1992;Weinberger, 1990;Wylie, 1979). The result is that indi-viduals often limit their awareness to include only those experiences congruent with, or distort representations of their experience to sustain, their conscious concept of self (S. Freud, 1914Freud, /1957Kernberg, 1967;Rogers, 1951).…”
mentioning
confidence: 99%
“…-a patient whose prior analysis had been a traditional one -the contemporary Chicago analyst Gedo (1980) harshly discounts the scientific quality of Kohut's case study material. -a patient whose prior analysis had been a traditional one -the contemporary Chicago analyst Gedo (1980) harshly discounts the scientific quality of Kohut's case study material.…”
Section: Resultsmentioning
confidence: 99%
“…Whatever we may think of the whole edifice of Kohut's theoryand many have suggested that it is structurally unsound (Gedo, 1980)-I believe that his conception of narcissistic rage and his perspective on the clinical approach to aggression are both internally consistent and of real clinical value.…”
Section: )mentioning
confidence: 98%